Optimization of recombinant human transferrin expression in insect cells baculovirus system - M. Ongkudon, Clarence (2006)
Insect cells-baculovirus expression system is a promising new artificial system for the production of many therapeutic glycoproteins. This system owns many of the protein processing and folding mechanisms of mammalian cells and is capable of expressing a large amount of recombinant proteins. This work aimed at expressing, optimizing, and characterizing recombinant human Transferrin (rhTf), a model glycoprotein, at a laboratory scale. In this research, time course expression profiles of rhTf at various multiplicities of infection (MOI), seeding densities (SD), times of infection (TOI), and harvest times (HT) were studied. Screening experiments were conducted to identify the medium components in Sf900-II SFM and the recombinant baculovirus stock that resulted in improved production of rhTf. Finally, Response Surface Methodology (RSM) was employed to hunt for optimum medium composition. The results showed that the optimum HT for rhTf was between 24 to 72 hours post infection, at SD of 1.6 x 106 viable cells/ml, TOI of day 2 post seeding, and MOI of 5 pfu/cell. Glucose and glutamine were found to have the most positive effect on rhTf production with more than 95% significance. In addition to that, the best recombinant baculovirus stock was identified at 98.7% purity. With the optimized parameters, rhTf production had increased three-fold from 19.89Î¼g/ml to 65.12Î¼g/ml.